Addition of Navitoclax to Ongoing Ruxolitinib Therapy for Patients With Myelofibrosis With Progression or Suboptimal Response: Phase II Safety and Efficacy. Issue 15 (20th May 2022) - Harrison, Claire N.; Garcia, Jacqueline S.; Somervaille, Tim C.P.; Foran, James M.; Verstovsek, Srdan; Jamieson, Catriona; Mesa, Ruben; Ritchie, Ellen K.; Tantravahi, Srinivas K.; Vachhani, Pankit; O'Connell, Casey L.; Komrokji, Rami S.; et al.
Abstract : PURPOSE: Targeting the BCL-XL pathway has demonstrated the ability to overcome Janus kinase inhibitor resistance in preclinical models. This phase II trial investigated the efficacy and safety of adding BCL-XL /BCL-2 inhibitor navitoclax to ruxolitinib therapy in patients with myelofibrosis with progression or suboptimal response to ruxolitinib monotherapy (ClinicalTrials.gov identifier: NCT03222609 ). METHODS: Thirty-four adult patients with intermediate-/high-risk myelofibrosis who had progression or suboptimal response on stable ruxolitinib dose (≥ 10 mg twice daily) were administered navitoclax at 50 mg once daily starting dose, followed by escalation to a maximum of 300 mg once daily in once in weekly increments (if platelets were ≥ 75 × 10 9 /L). The primary end point was ≥ 35% spleen volume reduction (SVR35 ) from baseline at week 24. Secondary end points included ≥ 50% reduction in total symptom score (TSS50 ) from baseline at week 24, hemoglobin improvement, change in bone marrow fibrosis (BMF) grade, and safety. RESULTS: High molecular risk mutations were identified in 58% of patients, and 52% harbored ≥ 3 mutations. SVR35 was achieved by 26.5% of patients at week 24, and by 41%, at any time on study, with an estimated median duration of SVR35 of 13.8 months. TSS50 was achieved by 30% (6 of 20) of patients at week 24, and BMF improved by 1-2 grades in 33% (11 of 33) of evaluable patients. Anemia response was achieved by 64% (7 of 11), including one patient with baseline transfusion dependence. Median overall survival was not reached with a median follow-up of 21.6 months. The most common adverse event was reversible thrombocytopenia without clinically significant bleeding (88%). CONCLUSION: The addition of navitoclax to ruxolitinib in patients with persistent or progressive myelofibrosis resulted in durable SVR35, improved TSS, hemoglobin response, and BMF. Further investigation is underway to qualify the potential for disease modification. Abstract : Novel Combo: Navitoclax plus Rux for patients w/MF and poor Rux response ïƒ improved SVR, TSS, and BMF | #MPNSM